Geo-informatics in sustainable ecosystem and society : 6th international conference, GSES 2018, Handan, China, September 25-26, 2018, revised selected papers /: 6th international conference, GSES 2018, Handan, China, September 25-26, 2018, revised selected papers. (2019) - Unknown
No abstract available